2011
DOI: 10.2174/187152811798104917
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Stage of Allergic Rhinitis is Correlated to Inflammation as Detected by Nasal Cytology

Abstract: Allergic rhinitis (AR) is the most common allergic disease. The Allergic Rhinitis and its Impact on Asthma (ARIA) guidelines classify AR according to its duration and severity and suggest recommended treatments, but there is evidence that these guidelines are insufficiently followed. Considering the validity of histopathological data, physicians are more likely to be persuaded by such information on AR. Thus, we attempted to define the severity of AR by nasal cytology on the basis of the ARIA classification. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Our data confirm that the type of inflammation influences the clinical features, and in particular the severity of symptoms and risk of comorbidities. In our opinion, nasal cytology is a very useful test in outpatient clinical rhinological evaluation, allowing for correct differential diagnosis of various forms of NAR (31)(32)(33)(34)(35) . Its impact on differential diagnosis is valuable as it allows identification of patients with NAR who have a significantly reduced quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…Our data confirm that the type of inflammation influences the clinical features, and in particular the severity of symptoms and risk of comorbidities. In our opinion, nasal cytology is a very useful test in outpatient clinical rhinological evaluation, allowing for correct differential diagnosis of various forms of NAR (31)(32)(33)(34)(35) . Its impact on differential diagnosis is valuable as it allows identification of patients with NAR who have a significantly reduced quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…This was obtained in patients sensitized to grass pollen. In a study on 64 patients with grass pollen-induced AR, 22 patients (34.4%) had mild intermittent, 21 (32.8%) had moderate-to-severe intermittent, ten (15.6%) had mild persistent, and eleven (17.2%) had moderate-to-severe persistent AR 12. Nasal cytology detected neutrophils in 49 patients, eosinophils in 41 patients, mast cells in 21 patients, and lymphocytes or plasma cells in 28 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The following steps characterize the cytological technique: sampling, processing (with fixing and staining), and observation through microscopy. The cytological sampling consists of collecting the nasal mucosa surface cells by the Rhino-probe (Arlington Scientific, Springville, UT, USA) 12. The sampling step must be carefully performed through anterior rhinoscopy, using a nasal speculum and good lighting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ARIA classification redefined the criteria for identifying the phenotype of patients with AR, by the duration – intermittent or persistent – regardless of the season, and the severity of symptoms with their impact in daily life, classified as mild and moderate-to-severe [9]. Recent studies showed that the ARIA severity classification clearly discriminates the impact of AR in all domains of quality of life and categorized symptom score [16], and that the ARIA classification was correlated with the nasal cytology, which showed different cell types and counts according to different severity, with higher counts of mast cells and lymphocyte/plasma cells in moderate-to-severe AR [17]. The SURF study was aimed at investigating the features of AR in a large population of children and adults.…”
Section: Discussionmentioning
confidence: 99%